Epitope Capsid-Incorporation: New Effective Approach for Vaccine Development for Chagas Disease - Qiana L. Matthews; Anitra L. Farrow; Girish Rachakonda; Linlin Gu; Pius Nde; Alexandre Krendelchtchikov; Siddarth Pratap; Shruti S. Sakhare; Steffanie Sabbaj; Maria F. Lima; Fernando Villalta (Case Western Reserve University, 2016)
Background: Previously we reported that a hexon-modified adenovirus (Ad) vector containing the invasive neutralizing epitope of Trypanosoma cruzi (T. cruzi) trypomastigote gp83 (Ad5-gp83) provided immunoprotection against T. cruzi infection. The purpose of this work was to design an improved vaccine for T. cruzi using a novel epitope capsid incorporation strategy. Thus, we evaluated the immunoprotection raised by co-immunization with Ad5-gp83 and an Ad vector containing an epitope (ASP-M) of the T. cruzi amastigote surface protein 2. Methods: Protein IX (pIX)-modified Ad vector (Ad5-pIX-ASP-M) was generated, characterized, and validated. C3H/He mice were immunized with Ad5-pIX-ASP-M and Ad5-gp83 and the cell-mediated responses were evaluated by enzyme-linked immunospot (ELISPOT) assay and intracellular staining. Immunized mice were challenged with T. cruzi to evaluate the vaccine efficacy. Results: Our findings indicate that Ad5-pIX-ASP-M was viable. Specific CD8+ T-cell mediated responses prior to the challenge show an increase in IFNγ and TNFα production. A single immunization with Ad5-pIX-ASP-M provided protection from T. cruzi infection, but co-immunizations with Ad5-pIX-ASP-M and Ad5-gp83 provided a higher immunoprotection and increased survival rate of mice. Conclusions: Overall, these results suggest that the combination of gp83 and ASP-M specific epitopes onto the capsid-incorporated adenoviruses would provide superior protection against Chagas disease as compared with Ad5-gp83 alone.